The Romance Between NCTzen and NCT: Commodifying Fan Relationships on the Bubble App - Salijar, Hasna Qhotrunnadaa; Gelgel, Ni Made Ras Amanda; Pradipta, Ade Devia (Institut Komunikasi dan Bisnis LSPR, 2025)
This study aims to understand how NCT's romance is commodified through the Bubble application. It employs a qualitative approach with a constructivist perspective. Informants were chosen based on their availability and willingness. Data were gathered from two sources: primary and secondary. Primary data were collected through interviews with informants and participant observation on the Bubble app, while secondary data were derived from relevant previous literature. The research data were analyzed in several stages: data reduction, data presentation, conclusion drawing, and verification. The study found that SM Entertainment, the media owner, recognizes the desire of NCTZen to have a closer connection with NCT. Consequently, SM Entertainment engages in three forms of commodification through the Bubble application: romantic content, labor, and audience. This commodification results in significant benefits for SM Entertainment due to the loyalty of NCTZen towards NCT.